Association of Abnormal P‐Wave Indices With Dementia and Cognitive Decline Over 25 Years: ARIC‐NCS (The Atherosclerosis Risk in Communities Neurocognitive Study). Issue 24 (17th December 2019) - Gutierrez, Alejandra; Norby, Faye L.; Maheshwari, Ankit; Rooney, Mary R.; Gottesman, Rebecca F.; Mosley, Thomas H.; Lutsey, Pamela L.; Oldenburg, Niki; Soliman, Elsayed Z.; Alonso, Alvaro; Chen, Lin Y.
Abstract : Background: Abnormal P‐wave indices (PWIs)—reflecting underlying left atrial abnormality—are associated with increased risk of stroke independent of atrial fibrillation. We assessed whether abnormal PWIs are associated with incident dementia and greater cognitive decline, independent of atrial fibrillation and ischemic stroke. Methods and Results: We included 13 714 participants (mean age, 57±6 years; 56% women; 23% black) who were followed for dementia through the end of 2015. (Abnormal P‐wave terminal force in lead V1, ≥4000 μV×ms), abnormal P‐wave axis (>75° or <0°), prolonged P‐wave duration (>120 ms), and advanced interatrial block were determined from ECGs at visits 2 to 4. Dementia was adjudicated by an expert panel using data from cognitive tests and hospitalization International Classification of Diseases codes. Cognitive function was measured longitudinally using 3 neuropsychological tests. Cox proportional hazards models were used to assess the association between time‐dependent abnormal PWIs with incident dementia. Linear regression models were used to evaluate PWIs with cognitive function over time. At the conclusion of the study, 19%, 16%, 28%, and 1.9% of participants had abnormal P‐wave terminal force in lead V1, abnormal P‐wave axis, prolonged P‐wave duration, and advanced interatrial block, respectively. During mean follow‐up of 18 years, there were 1390 (10%) dementia cases. All abnormal PWIs except advanced interatrial block were associated with an increased risk of dementia even after adjustment for incident atrial fibrillation and stroke: multivariable hazard ratio of abnormal P wave terminal force in lead V1=1.60, 95% CI, 1.41 to 2.83; abnormal P‐wave axis, hazard ratio =1.36, 95% CI, 1.17 to 2.57; prolonged P‐wave duration, hazard ratio=1.60, 95% CI, 1.42 to 1.80. Only abnormal P‐wave terminal force in lead V1 was associated with greater decline in global cognition. Conclusions: Abnormal PWIs are independently associated with an increased risk of dementia. This novel finding should be replicated in other cohorts and the underlying mechanisms should be evaluated.